EUS-guided treatment of gastric fundal varices with combined injection of coils and cyanoacrylate glue: a large U.S. experience over 6 years (with video) - Bhat, Yasser M.; Weilert, Frank; Fredrick, R. Todd; Kane, Steven D.; Shah, Janak N.; Hamerski, Chris M.; Binmoeller, Kenneth F. (Gastrointestinal endoscopy, 2016)
Conventional endoscopic treatment of gastric fundal varices (GFV) with cyanoacrylate (CYA) glue may be complicated by embolization and rebleeding. We evaluated the long-term outcomes of EUS-guided injection of coils and CYA glue for therapy of GFV. A retrospective chart review of patients treated for GFV was performed. The main outcomes measured were hemostasis, obliteration on surveillance EUS, post-treatment bleeding rate, and adverse events. From March 2009 to 2015, 152 patients with GFV were treated. Seven (5%) had active hemorrhage, 105 (69%) had recent bleeding, and 40 (26%) were treated for primary prophylaxis. Treatment was technically successful in 151 patients (>99%). Mean number of coils was 1.4 (range, 1-4 coils), and mean volume of CYA was 2 mL (range, 0.5-6). Follow-up was available for 125 patients with treated GFV (mean, 436 days; range, 30-2043). Among 100 patients with follow-up EUS examinations, complete obliteration (on Doppler study) of GFV was confirmed in 93 (93%). Post-treatment bleeding from obliterated GFV occurred in 3 of 93 patients (3%). Twenty-five patients who had clinical and/or EGD follow-up had 3 post-treatment bleeding episodes after a median follow-up of 324 days (range, 41-486). Among the 40 patients treated for primary prophylaxis, 28 underwent follow-up EUS and 27 (96%) had confirmed obliteration. Mild postprocedure abdominal pain occurred in 4 of 125 patients (3%), and clinical signs of pulmonary embolization were seen in 1 patient (1%). Another 4 of 125 patients (3%) presented with minor delayed upper GI bleeding from coil/glue extrusion. EUS-guided combined coil and CYA glue injection of high-risk GFV appears to be highly effective for hemostasis in active bleeding and primary and secondary bleeding prophylaxis. Once obliteration was achieved, post-treatment bleeding from GFV occurred in only 3% during long-term follow-up. Combination therapy appears safe and may reduce the risk of CYA embolization.